2019
DOI: 10.1039/c9sc04708e
|View full text |Cite
|
Sign up to set email alerts
|

Screening of metal ions and organocatalysts on solid support-coupled DNA oligonucleotides guides design of DNA-encoded reactions

Abstract: Screening of metal ions and organocatalysts on solid support-coupled DNA oligonucleotides guides design of DNA-encoded reactions DNA-encoded compound libraries are a widely used technology for target-based small molecule screening. Initiating encoded compound synthesis with solid phase -coupled DNA barcodes does benefi t from choice of organic solvents. Screening of more than 50 metal salts and organic reagents for DNA compatibility suggested reactions for encoded compound synthesis. A ZnCl2-mediated aza-Diels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 69 publications
1
39
0
8
Order By: Relevance
“…In this reaction we observed that the most lipophilic micelles ( IC a , ID , IID , and IIE ) yielded less of the desired product DNA‐15 , but significantly less DNA‐depurination. To confirm product formation, we compared the micelle‐mediated Biginelli reaction to DNA‐15 with the previously reported Biginelli reaction on a controlled pore glass (CPG) solid support (Figure S110) [10] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this reaction we observed that the most lipophilic micelles ( IC a , ID , IID , and IIE ) yielded less of the desired product DNA‐15 , but significantly less DNA‐depurination. To confirm product formation, we compared the micelle‐mediated Biginelli reaction to DNA‐15 with the previously reported Biginelli reaction on a controlled pore glass (CPG) solid support (Figure S110) [10] …”
Section: Resultsmentioning
confidence: 99%
“…To confirm product formation, we compared the micelle-mediated Biginelli reaction to DNA-15 with the previously reported Biginelli reaction on a controlled pore glass (CPG) solid support (Figure S110). [10] Micelle ID was then selected to perform the Biginelli reaction on a small scope of aldehydes (Figures S112-S115…”
Section: Impact Of Copolymer Structure On the Reaction Kinetics Of On-dna Povarov Reaction Boc Protective Group Removal And Biginelli Reamentioning
confidence: 99%
See 2 more Smart Citations
“… 10 One reason for this limitation is that the scope of chemical reactions applicable in solution-phase DEL libraries are constrained to robust reactions that preserve the integrity of the oligonucleotides; few new synthetic methodologies can be applied to DEL library construction. 11 To preserve the integrity of the DNA barcodes, chemists have continued to expand the scope of mild chemical transformations and DNA-protecting strategies (solid-phase DEL, 12 reversible absorption of DNA onto resin, 13 micellar catalyst-promoted reactions 14 ), which provides new opportunities for DEL library synthesis.…”
Section: Introductionmentioning
confidence: 99%